The new education : how to revolutionize the university to prepare students for a world in flux - Davidson, Cathy N., 1949- (New York : Basic Books, 2017)
A leading educational thinker argues that the American university is stuck in the past--and shows how we can revolutionize it to prepare students for our age of constant change
Introduction -- Quarter life crisis -- College for everyone -- Against technophobia -- Against technophilia -- Palpable impact -- Why college costs so much -- The measure of a student -- The future of learning.
Includes bibliographical references and index.
Complimentary copy from PDC
Keywords: Education, Higher -- Aims and objectives; Educational change